Contemporary Strategy Theory and Practice: A Summary of the Literature - Eka Pria (PT. Publikasiku Academic Solution, 2025)
Contemporary strategy continues to evolve along with changes in the global environment, technology, and market dynamics. Modern strategic approaches now involve more than just classic theories such as Resource-Based View (RBV) and Dynamic Capabilities; they include new concepts more adaptive to the disruption of the times. This research uses a descriptive qualitative approach with a literature review method. The literature reviewed included scientific journals, books, and research reports relevant to contemporary strategy theory and practice. From the results of the literature review, eight main contemporary strategy approaches were found: Optimal Distinctiveness, Cultural Entrepreneurship, the role of emotions and ambiguity in organizations, Attention-Based View, business divestment, Strategic Rhythms, and the integration of artificial intelligence (AI) in strategy development. Each approach offers a unique contribution to understanding organizational strategy in an era of complexity and disruption. This research confirms that no single theory of strategy is universally applicable. Contextual incorporation of various contemporary approaches is essential to develop adaptive and competitive strategies. This research also opens up further research opportunities for empirical validation and cross-theoretical integration in strategic practice.